Alternative Dispute Resolution (ADR) in resolving community disputes in Pakistan: learning from Malaysia’s experience - Khan, Ihtesham Ullah; Mohamed, Nurah Sabahiah; Omoola, Sodiq (IIUM Press, 2025)
Disputes are ubiquitous in human societies, spanning across individuals, families, tribes, and nations. In Pakistan, various provinces have developed traditional dispute resolution mechanisms: the Jirga system for the Pushtoon community, Panchayat for Punjabis, Faislo among Sindhis, and Balochi Jirga for Balochis. These systems, rooted in cultural practices, have historically facilitated justice and harmony. However, they have faced criticism for their reliance on unwritten rules, informal structures, and violations of human and women's rights. This article explores the nature of these traditional systems in Pakistan, analysing their methods of dispute resolution and their effectiveness in administering justice. The study adopts a qualitative methodology, using doctrinal and library-based legal research, along with a comparative analysis of community dispute resolution in Pakistan and Malaysia. It also proposes recommendations for enhancing these systems, drawing insights from Malaysia's successful community mediation programmes. Unlike Pakistan, Malaysia has formalised community mediation under